Library association as a bridge between the academic and the civil sector. - Horvat, Aleksandra knjižničarka (2008)
The relations between the academic field and the civil society in Croatia exist, but strangely enough have not always been recognized as such, especially not in the last two decades. Civil society has often and quite wrongly been (mis)understood as a group of organizations of local volunteers or specialized activist groups, gathered around a specific issue of interest which is in no way connected with profession or scholarship. Examples of civil society organizations would be associations of persons interested in women's or minority rights, ecological issues, or quality of urban life. Foundations as specific organizations with a philanthropic or humanitarian mission also belong to the civil sector, but their modest number and limited influence in the society cannot change much the overall impression of the civil society. Nevertheless, the fact that various professional associations exist in Croatia and that traditionally they have been called upon to provide advice and opinion when politicians have to deal with certain professional issues is often neglected. There is no doubt that professional associations are close to the civil sector, in spite of the fact that they might be and often are financed fully or at least in part by the government. In this paper the author will try to show how the activities of one such professional association - the Croatian Library Association - helped support and promote the library and information profession in the country and what kind of co-operation between the academic community, civil society organizations and the professional library association is feasible.
ENG